Beneficial Roles of Melatonin on Redox Regulation of Photosynthetic Electron Transport and Synthesis of D1 Protein in Tomato Seedlings under Salt Stress - Zhou, Xiaoting; Zhao, Hailiang; Cao, Kai; Hu, Lipan; Du, Tianhao; Baluška, František; Zou, Zhirong (Frontiers in Plant Science, 2016)
Melatonin is important in the protection of plants suffering various forms of abiotic stress. The molecular mechanisms underlying the melatonin-mediated protection of their photosynthetic machinery are not completely resolved. This study investigates the effects of exogenous melatonin applications on salt-induced damage to the light reaction components of the photosynthetic machinery of tomato seedlings. The results show that melatonin pretreatments can help maintain growth and net photosynthetic rate (PN) under salt stress conditions. Pretreatment with melatonin increased the effective quantum yield of photosystem II (ΦPSII), the photochemical quenching coefficient (qP) and the proportion of PSII centers that are ‘open’ (qL) under saline conditions. In this way, damage to the photosynthetic electron transport chain (PET) in photosystem II (PSII) is mitigated. In addition, melatonin pretreatment facilitated the repair of PSII by maintaining the availability of D1 protein that was otherwise reduced by salinity. The ROS levels and the gene expressions of the chloroplast TRXs and PRXs were also investigated. Salt stress resulted in increased levels of reactive oxygen species (ROS), which were mitigated by melatonin. In tomato leaves under salt stress, the expressions of PRXs and TRXf declined but the expressions of TRXm1/4 and TRXm2 increased. Melatonin pretreatment promoted the expression of TRXf and the abundances of TRXf and TRXm gene products but had no effects on the expressions of PRXs. In summary, melatonin improves the photosynthetic activities of tomato seedlings under salt stress. The mechanism could be that: (1) Melatonin controls ROS levels and prevents damaging elevations of ROS caused by salt stress. (2) Melatonin facilitates the recovery of PET and D1 protein synthesis, thus enhancing the tolerance of photosynthetic activities to salinity. (3) Melatonin induces the expression of TRXf and regulates the abundance of TRXf and TRXm gene products, which may facilitate repair of the light reaction parts of the photosynthetic machinery.